Modern Methods for the Diagnosis of Morphological and Functional Features of the Retina in Dysbinocular and Anisometropic Amblyopia - R. R. Khubieva; E. P. Tarutta (Oftalʹmologiâ, 2022)
Child health is a global health priority. Anomalies of refraction, complicated by amblyopia and squint, occupy one of the leading places in the pathology of the visual system of children. According to data obtained from 26 regions of Russia, the leading place in the ocular morbidity of children and adolescents is occupied by ametropia and strabismus with amblyopia. They account for up to 90 % of all cases of visual impairment in childhood. The term amblyopia is understood to mean a decrease in the maximum corrected visual acuity that occurred at an early age, which is caused by disorders of the functions of the visual analyzer, without changes in the fundus and organic lesions of the visual pathways and centers. Despite the outstanding achievements of 21st century medicine, today the questions of the pathophysiological essence of this condition remain open, which is the subject of discussions among pediatric ophthalmologists around the world. In this regard, the literature review presents the results of domestic and foreign authors who studied the morphological (optical coherence tomography) and functional (electroretinography, microperimetry) features of the retina in dysbinocular and anisometropic amblyopia. Some authors have demonstrated the presence of differences in the thickness of the central region and the layer of nerve fibers in patients with amblyopia compared with paired and healthy eyes, their correlation with functional parameters, as well as changes in the thickness of the choroid and microvasculature of the retina. Recently, there have been works devoted to the study of the photosensitivity of the retina in patients with amblyopia and visual rehabilitation using this equipment. A number of authors have shown that with amblyopia, the retinal photosensitivity parameters in the central region are reduced, and there is a correlation between these changes and morphological changes in the posterior pole. The microperimeter also makes it possible to carry out visual rehabilitation, in particular in pediatric patients, and isolated results have been published on the use of this method in patients with amblyopia. The literature data are quite contradictory, and more research remains to be done to determine whether these changes in the retina are primary in relation to this disease, or whether they can be the result of retrograde changes that are obscured by defocusing of visual images from birth.